Autoimmune Pancreatitis Presenting a Short Narrowing of Main Pancreatic Duct with Subsequent Progression to Diffuse Pancreatic Enlargement over 24 Months; Natural History of Autoimmune Pancreatitis - Umemura, Shuichiro; Naitoh, Itaru; Nakazawa, Takahiro; Hayashi, Kazuki; Miyabe, Katsuyuki; Shimizu, Shuya; Kondo, Hiromu; Nishi, Yuji; Yoshida, Michihiro; Hori, Yasuki; et al. (JOP. Journal of the Pancreas, 2014)
Context Initial pancreatogram and natural history of autoimmune pancreatitis (AIP) have not been clarified, and there were few recent studies concerning the association between AIP and intraductal papillary mucinous neoplasm (IPMN). Case report We report an 81-year- old man with AIP associated with IPMN. Although the initial pancreatogram was normal, a short narrowing of the main pancreatic duct (MPD) appeared during a follow-up for IPMN after 6 months, which was highly suggestive of pancreatic cancer. A narrowing of the MPD extended after 15 months, and this progressed to diffuse narrowing of the MPD with an elevation in the serum IgG4 levels after 24 months. Finally, the patient was diagnosed with diffuse-type AIP, according to the Japanese diagnostic criteria 2011 and the International Consensus Diagnostic Criteria. Considering the natural history of AIP, this marked change of the MPD is indicative of this condition. Conclusion We report a case of AIP presenting with a short narrowing of the MPD with subsequent progression to diffuse pancreatic enlargement during a follow-up for IPMN. Image: Remarkable change of main pancreatic duct.